Islamic Religious Organizations Across Borders: The Case of the Pakistani Migrant Muslim Community in Korea (South). Issue 2 (2nd April 2016) - Shahzad, Muhammad; Lee, Hee Soo
Abstract: With the formation of small migrant communities in foreign lands, some religious organizations migrate along with the migrants and play a part in shaping and reshaping the socio-religious experiences of respective migrants. This paper looks into how Islamic religious organizations have been established in South Korea; how the socio-religious experience of the Pakistani Muslim minority community in Korea is mediated by these organizations; and what is the impact of this mediation on the daily socio-religious lives of the migrants. Two Islamic religious organizations—Dawat-e-Islami and Minhaj-ul-Quran—have been discussed here which originated in Pakistan and have been working around the world including Korea. Using the conceptual framework of social capital, we elaborate on three stages for establishment and working of these religious institutions: deployment of social capital for initiation; reinforcement of social capital for establishment; and sustenance with social capital over a course of time. This paper proposes that these religious organizations are established by the migrant community because of the social capital created within, as opposed to any master plan from the respective parent organizations in the country of origin. Further, these organizations become connected to mainstream organizations as a result of community efforts.